Differentiating Oneiric Stupor in Agrypnia Excitata From Dreaming Disorders - Baldelli, Luca; Provini, Federica (Frontiers in Neurology, 2020)
Oneiric Stupor (OS) in Agrypnia Excitata represents a peculiar condition characterized by the recur-rence of stereotyped gestures such as mimicking daily-life activities associated with the re-porting of a dream mentation consisting in a single oneiric scene. It arises in the context of a completely disor-ganized sleep structure lacking any physiological cyclic organization, thus, going beyond the con-cept of abnormal dream. However, a proper differential diagnosis of OS, in the complex world of the “disorders of dreaming” can become quite challenging. The aim of this review is to provide use-ful clinical and videopolygraphic data on OS to differentiate it from other dreaming disorders. Each entity will be clinically evaluated among the areas of dream mentation and abnormal sleep behaviors and its polygraphic features will be analyzed and distinguished from OS.